Da’wa Method Ning Umi Laila in Youtube Video “Ibu ibu Luweh Seneng Pengajian Opo Rasan-Rasan” - Pipin Seltika (Program Studi Komunikasi dan Penyiaran Islam UIN Raden Fatah Palembang, 2023)
The more advanced the age then, the way of delivering the message also becomes more modern and follow the trend that evolves amongst the society. The same is true of the preachers who have different methods so that their message can be accepted by their mad’s. In this rapid development of technology many electronic media can be used as a means of distribution of fame like Youtobe, Tik tok, Instagram, Facebook and so on. This research was used to find out the method of praise of Ning Umi Laila in her YouTube video entitled